2021
DOI: 10.3233/jad-201022
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Identification in Subjective Cognitive Decline: A Meta-Analysis

Abstract: Background: Recently, subjective cognitive decline (SCD) has been considered to be one of the first signs of Alzheimer’s disease (AD). Since this potential early marker is sensitive but not specific to AD, combining it with other markers could ensure higher accuracy when predicting which persons with SCD will convert to AD. Since olfactory dysfunction is observable in both AD and mild cognitive impairment (MCI), it is a promising marker that could help improve the early diagnosis of AD. Objective: The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…evaluating OF in individuals with subjective cognitive decline and in healthy older adults found that there was a significant difference, with slight relative impairment in patients with subjective cognitive decline. 668 In the Mayo Clinic Study of Aging, participants were classified as having normal cognition, amnestic MCI, nonamnestic MCI, or dementia. This population-based prospective cohort study found that olfactory impairment is associated with amnestic MCI and the progression of amnestic MCI to AD dementia.…”
Section: J Related To Neurodegenerative Diseasementioning
confidence: 99%
“…evaluating OF in individuals with subjective cognitive decline and in healthy older adults found that there was a significant difference, with slight relative impairment in patients with subjective cognitive decline. 668 In the Mayo Clinic Study of Aging, participants were classified as having normal cognition, amnestic MCI, nonamnestic MCI, or dementia. This population-based prospective cohort study found that olfactory impairment is associated with amnestic MCI and the progression of amnestic MCI to AD dementia.…”
Section: J Related To Neurodegenerative Diseasementioning
confidence: 99%
“…A previous meta-analysis summarizing the structural changes implicated in olfactory processing showed that patients with AD and MCI had smaller OB volumes and a smaller POC when compared to controls and that these volumetric reductions could be measured as early as the MCI stage (Jobin et al, 2021a ). Even altered olfactory identification function has been detected in subjective cognitive decline (SCD), a stage that occurs before MCI (Jobin et al, 2021b ). A recent study provided evidence that the amygdala (a component of the POC) functions as a shared neural substrate linking olfactory identification ability with cognitive function (Shao et al, 2021 ; Tan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…SCD has been linked to slightly impaired odor identification abilities, according to a recent meta-analysis ( Jobin, Zahal, et al, 2021 ). Although the participants who reported exclusively SCD did not show olfactory decline in our sample, the small group of individuals that reported SCD + SOI showed worse objective olfactory performance compared to both control and SCD groups.…”
Section: Discussionmentioning
confidence: 99%